The impact of acupuncture in the treatment of systemic arterial hypertension (Research, Society and Development, 2020)
Introduction: acupuncture can be indicated in isolation or as an adjunct, for the treatment of several chronic diseases, including in the control of hypertension. Objective: to identify the correlation of acupuncture practice as a treatment for systemic arterial hypertension. Methodology: this is an integrative review about acupuncture as a complementary health practice for hypertension. The search was carried out by consulting scientific articles from March to July 2019 in electronic databases, including articles published in full between the years 2013 and 2019. Results: of the 06 (six) selected articles, with 212 participants, 83.3% (5) were randomized clinical trials. And in which interventions are observed, use of magnetic resonance images, long-term monitoring and the effects of using the practice. Conclusion: it was evidenced in this review that acupuncture combined with pharmacological treatment can be effective in controlling hypertension.